2009
DOI: 10.1111/j.1600-0501.2009.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoconductivity of micro‐structured titanium implants (XiVE S CELLplus) by addition of surface calcium chemistry: a histomorphometric study in the rabbit femur

Abstract: The nano-structured Ca-incorporated oxide surface significantly enhanced osteoconductivity of micro-structured Ti implants in rabbit cancellous bone. Results indicate that this surface produced by simple hydrothermal treatment may be effective in improving the osseointegration of implants with micro-topographically complex surface structures in areas of loose cancellous bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
(85 reference statements)
9
49
0
1
Order By: Relevance
“…192 This method also caused incorporation of calcium as CaTiO 3 in the protective surface oxide layer. Titanium and Ti6Al4V implants with thus treated surfaces significantly increased BIC and removal torque forces in rabbit tibiae.…”
Section: In Vivo and Clinical Applicationsmentioning
confidence: 99%
“…192 This method also caused incorporation of calcium as CaTiO 3 in the protective surface oxide layer. Titanium and Ti6Al4V implants with thus treated surfaces significantly increased BIC and removal torque forces in rabbit tibiae.…”
Section: In Vivo and Clinical Applicationsmentioning
confidence: 99%
“…Several studies have reported important contributions from surface chemistry and micro-topography on osteogenesis [69][70][71][72][73][74] and Scaglione, Braccini, Wendt, Jaquiery, Beltrame, Quarto, and Martin in 2006 demonstrated osteogenesis on a 3D ceramic scaffold in the absence of defined osteo-inductive molecules [75]. This together Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Gao et al fabricated a micro/nanostructured porous surface on titanium and observed increased hydroxyapatite formation [32], and Kubo [14] and Zinger [33] found that microscale and nanoscale topography of the implant surface exhibited a synergistic effect on bone marrow osteoblasts and human-bone-derived MG63 cells proliferation. Furthermore, Park et al showed that the nanostructured Ca-incorporated oxide layer produced by hydrothermal treatment on microstructured titanium implants surface was effective in improving the osseointegration of implants in areas of loose cancellous bone [34].…”
Section: Discussionmentioning
confidence: 99%